Peran dan Fungsi Bahasa dalam Menunjang Kehidupan Manusia di Era Industri 4.0 dan Abad 21: Peran dan Fungsi Bahasa dalam Menunjang Kehidupan Manusia di Era Industri 4.0 dan Abad 21 - Hikma Tullaili; Silvina Noviyanti; Dinda Fatimah Azahra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Language is a vital element in human life, serving as the main tool for conveying ideas, feelings, and information. In the era of Industry 4.0 and the 21st century, language has undergone significant transformation due to advancements in digital technology and globalization. Its function has expanded beyond traditional spoken and written communication, becoming a critical instrument in technology, education, business, and cultural preservation. Mastery of adaptive language skills and digital literacy is essential to meet the challenges of complex communication in the modern world. This study employs a literature review method to analyze the role and function of language in contemporary contexts. The findings confirm that language is a key factor in building an inclusive, competitive digital society capable of adapting to technological and social changes.